Are Factors Associated with Adult Refugees’ Settlement different from Well-Being? A Longitudinal Study focusing on Gender and Age in Australia - Mahadevan, Renuka; Jayasinghe, Maneka (My University, 2022)
Using three waves of data and tracing the same refugees over time, this paper shows that some factors associated with settlement experience are different from life satisfaction. Evidence shows that although settlement experience has not improved over time, life satisfaction of both male and female refugees has. The non-linear effect of age on life satisfaction disappears over time while that of settlement experience lingers on. Discrimination affects both male and female life satisfaction but is only a concern for females and the younger cohort’s settlement experience. Psychological capital did not appear to moderate the discrimination effect, but this needs to be robustly examined further. Lastly, different support for refugees over time and a targeted focus on some groups is likely to be more effective than a blanket support policy.
Journal of Social Policy
Keywords: Health and wellbeing; Migration and settlement